Surgical morbidity and clinical outcomes in ovarian cancer – the role of obesity. (2nd September 2015) - Smits, A; Lopes, A; Das, N; Kumar, A; Cliby, W; Smits, E; Bekkers, R; Massuger, L; Galaal, K
Abstract : Objective: To evaluate the effect of body mass index on the surgical outcomes in ovarian cancer patients. In addition, we performed a systematic review to compare our outcomes with the current literature. Design: Retrospective cohort study and a systematic review of the literature. Setting: Gynaecology department at the Royal Cornwall Hospital Trust. Population: Surgically managed stage I‐IV ovarian cancer patients between September 2006 and September 2014. Methods: Primary and secondary outcome measures were evaluated across BMI categories; BMI <25 kg/m², BMI 25–29.9 kg/m², BMI ≥30 kg/m² and BMI ≥40 kg/m². A systematic review was performed according to Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines. Main outcome measures: The primary outcome measure was surgical complications. Secondary outcome measures were other intra‐ and postoperative outcomes. Results: Two hundred twenty‐eight women were included in the study, of which 84 had a BMI <25 kg/m², 84 women had a BMI 25–29.9 kg/m², and 60 women were obese (BMI ≥30 kg/m²), 13 of whom were morbidly obese. Morbid obesity was associated with increased rates of wound complications. However, BMI did not show an association with other outcomes. In the review, an increasing BMI was associated with increased rates of wound complications and prolonged hospital stay, but did not impact other surgical outcomes. Conclusion: Obesity is associated with increased rates of wound complications and a prolonged hospital stay, but does not appear to affect other operative outcomes including cytoreduction status and 30‐day mortality. Therefore, operative management and postoperative care require a multifactorial approach to minimise adverse outcomes. Tweetable abstract: Obesity is associated with more wound complications and prolonged hospital stay in ovarian cancer surgery. Tweetable abstract: Obesity is associated with more wound complications and prolonged hospital stay in ovarian cancer surgery.